Development of a canva-based heyzine flipbooks e-module as an alternative learning resources on pancasila education subjects - Nainggolan, Maniar Clarita; Rachman, Fazli (Universitas Tanjungpura, 2024)
The purpose of this research is that the learning materials used by teachers in the learning of Pancasila Education are judged to be boring, less interesting, difficult, confusing and cause students' knowledge to be less than maximum. The purpose of this study is to develop Canva-based Heyzine Flipbooks e-module learning media on smartphones/laptops as a Pancasila Education learning medium as well as find out the feasibility and assessment of Canva-based Heyzine Flipbooks e-module as an alternative learning resource on Pancasila Education subject. This study was conducted at SMA Negeri 1 Percut Sei Tuan. The subjects of the study were class XI-Matlanfor students at Percut Sei Tuan Secondary School 1, and this study used the research and development method developed by Willis. The development model used was R2D2.Questionnaires, interviews, observation and documentation were used as data collection techniques in this study. Data analysis technique This study used both qualitative and quantitative methods of analysis. The qualitative data of this study were obtained from validators, subject matter experts and the media at the validation stage. Quantitative constitutes data describing the results of product development in the form of e-module-based learning media Heyzine Flipbooks based on Canva. The obtained data were then analyzed using the formula of validity percentage(%) = tse/tsh x 100. The results of the study stated that the heyzine flipbooks on E-module learning were perceived as very useful and very interesting to use in the field because of the research data obtained from media experts, subject matter experts,PPKn teachers and student responses were declared very viable categories with the acquisition of subject matter expert validation of 98%, media expert validation of 98% and teacher evaluation of 96%. The very feasible category was then reinforced with a student response of 93% with the very interesting category. This proves that learning media is highly recommended to be applied in SMA Negeri 1 Percut Sei Tuan